Microplastics in freshwaters: Comparing effects of particle properties and an invertebrate consumer on microbial communities and ecosystem functions - Ze Hui Kong; Tong Liu; Francis J. Burdon; Amélie Truchy; Martyn Futter; Mirco Bundschuh; Rachel Hurley; Stefan Bertilsson; Brendan G. Mckie (Ecotoxicology and Environmental Safety)
The effects of microplastic (MP) accumulation in freshwaters on organisms and ecosystem functions are poorly understood, as are the roles of MP particle properties in regulating these effects. In freshwater microcosms, we quantified variation in microbial communities and ecosystem functions and compared effects of MP concentration (0, 1000, 50000 particles/kgsediment), shape (sphere, fragment, fibre), and polymer (polyethylene, polyethylene terephthalate, polypropylene, polystyrene) with those of a model invertebrate consumer (Chironomus riparius). We detected multiple effects of specific MP properties, especially associated with MP fragments and fibres, and the polymer polypropylene. These effects included increases in microbial abundance, consumer biomass and ecosystem respiration, as well as decreases in microbial enzyme activity and water chlorophyll-a. MP presence was also associated with increased relative abundance of microbial taxa reported to degrade plastics. However, consumer presence mostly had stronger effects (effect sizes ranging from ± 11 −313 %) than MP exposure (effect sizes ranging from ± 1–89 %) on microbial communities and ecosystem functions. Furthermore, several MP effects were only detected when chironomid consumers were absent. Overall, our findings suggest that MP effects on microbes and ecosystem functions are often relatively small and variable, depending on particle properties and consumer presence. Nevertheless, the number of MP effects detected highlights the need for further investigations of interactions between MPs and other environmental drivers, to more thoroughly assess the risks of MP pollution for freshwater ecosystems.